Isolation and Potency Test of Sulfate Reducing Bacteria (SRB) as Bioremediation Agent for Ex-Coal Mining Soil - Aria Yanka Paula Putri; Hary Widjajanti; Harminuke Eka Handayani (Sriwijaya Journal of Environment, 2020)
Mining activities can have negative impact on the environment causing water and soil pollution. Chemical physical properties also biological environment to change condition to be low organic matter, low soil pH, low water holding capacity, inadequate nutrient and acid generating material. Coal mining land is acidic cause of sulfur oxidation reaction with rainwater to produce sulfuric acid so that acidic of the soil condition. Biotechnology study is a wise effort to solution environment pollution with Sulfate Reducing Bacteria (SRB) as bioremediation agents. SRB can contaminate sulphate with an indicator pH increase which indicates of a SRB population increase and sulfate content decrease. This study aims to obtain a SRB isolate as potential a bioremediation agent for ex-coal mining soil. This study is experiment research with SRB isolate as treatment, that obtained from ex-coal mining soil at PT. Bukit Asam Tanjung Enim, South Sumatera. The result of this study obtained 10 (ten) SRB isolated a from the bacterial isolation stage. Ten SRB isolates were selected, obtained by five SRB isolates that have black criteria with the number of colonies approaching the same so that it has the potential as a bioremediation agent for ex-coal mining soil. SRB isolates P10T1R2, P9T2R2, P6T1R3, P5T1R1 dan P2T1R2 were potential tested on ex-coal mining to increase pH and reduce sulfate. The P5T1R1 SRB isolate has the potential to reduce sulfate at a concentration of 3561 ppm. Furthermore the result of the 5% LSD test show that this isolates is significantly different that other isolates so that it can be used as bioremediation agent.